Detection and antimicrobial resistance profile of campylobacter spp. in retail chicken meat from selected Davao City public markets - Durano, Lourivy P.
Campylobacter is one of the emerging foodborne pathogens alongside pathogenic Escherichia coli, Salmonella, Shigella and Trichinella (WHO, 2013). In particular, Campylobacter jejuni, a foodborne pathogen, is the most common cause of bacteria-mediated diarrheal disease worldwide and most studies have pointed out poultry and poultry products consumption as the primary risk factor in acquiring the infection (Yang, et al., 2003; Humphrey, et al., 2006; Wingstrand, et al., 2006). Aside from increasing human Campylobacter infections worldwide. The rapid emergence of antibiotic-resistant strains pose a threat in both medical and veterinary sectors (Alfredson & Korolik, 2007). Thus, this study was conducted to determine the presence and antimicrobial resistance profile of Campylobacter spp. In retail chicken meat from selected public markets in Davao City. A total of 136 out of 170 retail chicken meat tested, 80% (CI: 73.99-86.01) were found to be contaminated with Campylobacter spp. Althogether, the antimicrobial resistance profile of 134 isolates were determined. Of these , all isolates (100%) were resistant to tetrcycline, followed by erythromycine, 99.25%; ciprofloxacin, 98.51%; clindamycin, 97.76%; chloramphenicol, 70.15%; and gentamicin, 52.99%. Of the 134 isolates, 56 (41.79%) were found to be resistant to five antimicrobial agents, 53 (39.55%) were resistant to all antimicrobial agents, 22 (16.42%) were resistant to four antimicrobial agents. Consequently, all isolate were resistant to at least two antimicrobial agents tested and 97.76% (131 out of 134) were multi-drug resistant or resistant to four or more agents. These findings suggest the potential of chicken meat as a crucial vehicle of multi-drug resistant campylobacteriosis to susceptible host in Davao City and efforts to reduce the risk of acquiring this organism should be taken into consideration.